Упростите выражение: 3c^2-2/c+2 - c/c+2 : c/c^2-4 - 4c/c+2

Упростите выражение: 3c^2-2/c+2 - c/c+2 : c/c^2-4 - 4c/c+2
Гость
Ответ(ы) на вопрос:
Гость
3c^2-2/c+2 - c/c+2 : c/c^2-4 - 4c/c+2 =  = 3c^2-2/c+2 - c/c+2 * (c+2)(c-2)/c - 4c/c+2 = =3c^2 - 2/c+2 - (c -2) - 4c/c+2 = 3c^2-2 - (c-2)(c+2) - 4c =  3c^2-2 -c^2 + 4 - 4c =                                                             c+2                                c+2 = 2c^2 - 4c +2 = 2(c^2 -2c +1) = 2(c-1)^2         c+2                 c+2                 c+2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы